Case Study: Application of the Internet of Things (IoT) in the Manufacturing Industry in Indonesia - Josefa Flores; Catherine Li; Mariam Khan (Journal of Loomingulisus ja Innovatsioon, 2025)
The adoption of the Internet of Things (IoT) in the manufacturing industry has revolutionized production processes globally, offering enhanced automation, real-time monitoring, and improved decision-making. In Indonesia, however, the application of IoT in the manufacturing sector remains limited despite its potential to increase productivity and efficiency. The primary objective of this research is to assess the role of IoT in enhancing operational efficiency and productivity in Indonesia’s manufacturing industry. The study also aims to identify the barriers to IoT adoption and provide recommendations for overcoming these challenges. This study utilizes a case study approach, focusing on selected manufacturing companies in Indonesia that have integrated IoT technologies into their production processes. Data was collected through interviews, surveys, and site visits, supplemented by secondary data from industry reports. Qualitative and quantitative analysis techniques were applied to evaluate the findings. The research indicates that IoT implementation has led to significant improvements in process optimization, reduced downtime, and better resource management. However, challenges such as high initial costs, lack of skilled personnel, and resistance to change were identified as key obstacles hindering broader adoption. The findings highlight the transformative potential of IoT in Indonesia’s manufacturing sector.